PEMBUDAYAAN MUTU PENDIDIKAN DI SMK MA’ARIF NU 1 KECAMATAN AJIBARANG KABUPATEN BANYUMAS - Hartono hartono (Jurnal Penelitian Agama, 2017)
This research is a qualitative research aimed to know the steps undertaken in quality culture at SMK Ma'arif NU 1 Ajibarang District Banyumas Regency. The data in this study were collected by interview, observation, and documentation technique and then analyzed using data analysis technique in Miles and Huberman model field. The results showed that the steps taken by the principal in the culture of quality education include: (1) Building commitment of teachers and employees in improving the quality of education. (2) Communicate quality messages to teachers and employees. (3) Provide assurance that customer's voice, complaints or constructive criticism of the customer are heard and acted upon. (4) Do not blame teachers and employees in the event of errors or failures in the application of SOP and IK. (5) Directing innovations from teachers and employees to improve the quality of education. (6) Conduct assessment with appropriate mechanisms to determine achievement of quality objectives. (7) Embedding and embodying sincere value in working in the teachers and employees.